ՀՀ-ում արդյունավետ գործառող սոցիալական պաշտպանության համակարգի ստեղծման հնարավորությունները - Յարմալոյան Մարինե (Bulletin of Yerevan University G: Economics, 2017)
The article presents the main problems impeding the formation of effective functioning social protection system in RA. The author also suggests possible solutions to those problems.